The Yersinia enterocolitica Motility Master Regulatory Operon, flhDC, Is Required for Flagellin Production, Swimming Motility, and Swarming Motility - Young, Glenn M. (American Society for Microbiology, 1999)
The ability to move over and colonize surface substrata has been linked to the formation of biofilms and to the virulence of some bacterial pathogens. Results from this study show that the gastrointestinal pathogen Yersinia enterocolitica can migrate over and colonize surfaces by swarming motility, a form of cooperative multicellular behavior. Immunoblot analysis and electron microscopy indicated that swarming motility is dependent on the same flagellum organelle that is required for swimming motility, which occurs in fluid environments. Furthermore, motility genes such as flgEF, flgMN, flhBA, and fliA, known to be required for the production of flagella, are essential for swarming motility. To begin to investigate how environmental signals are processed and integrated by Y. enterocolitica to stimulate the production of flagella and regulate these two forms of cell migration, the motility master regulatory operon, flhDC, was cloned. Mutations within flhDC completely abolished swimming motility, swarming motility, and flagellin production. DNA sequence analysis revealed that this locus is similar to motility master regulatory operons of other gram-negative bacteria. Genetic complementation and functional analysis of flhDC indicated that it is required for the production of flagella. When flhDC was expressed from an inducible ptac promoter, flagellin production was shown to be dependent on levels of flhDC expression. Phenotypically, induction of the ptac-flhDC fusion also corresponded to increased levels of both swimming and swarming motility.